Exploring the Effects of Six Weeks of Resistance Training on the Fecal Microbiome of Older Adult Males: Secondary Analysis of a Peanut Protein Supplemented Randomized Controlled Trial - Johnathon H. Moore; Kristen S. Smith; Dongquan Chen; Donald A. Lamb; Morgan A. Smith; Shelby C. Osburn; Bradley A. Ruple; Casey D. Morrow; Kevin W. Huggins; James R. McDonald; Michael D. Brown; Kaelin C. Young; et al. (MDPI AG, 2022)
The bacteria inhabiting the gastrointestinal tract contribute to numerous host functions and can be altered by lifestyle factors. We aimed to determine whether a 6-week training intervention altered fecal microbiome diversity and/or function in older males. Fecal samples were collected prior to and following a 6-week twice-weekly supervised resistance training intervention in 14 older Caucasian males (65 ± 10 years, 28.5 ± 3.2 kg/m2) with minimal prior training experience. Participants were randomized to receive a daily defatted peanut powder supplement providing 30 g protein (n = 8) or no supplement (n = 6) during the intervention. Bacterial DNA was isolated from pre-and post-training fecal samples, and taxa were identified using sequencing to amplify the variable region 4 (V4) of the 16S ribosomal RNA gene. Training significantly increased whole-body and lower-body lean mass (determined by dual energy X-ray absorptiometry) as well as leg extensor strength (p < 0.05) with no differences between intervention groups. Overall composition of the microbiome and a priori selected taxa were not significantly altered with training. However, MetaCYC pathway analysis indicated that metabolic capacity of the microbiome to produce mucin increased (p = 0.047); the tight junction protein, zonulin, was measured in serum and non-significantly decreased after training (p = 0.062). Our data suggest that resistance training may improve intestinal barrier integrity in older Caucasian males; further investigation is warranted.